The Influence Of EPS And Sales Growth On Stock Prices In Sharia Property Companies Listed On The Indonesian Sharia Stock Index - Mutawali, Mutawali; Larasati, Ratih Dewi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
The study aims to determine and prove empirically the effect of Earning Per Share and Sales Growth on Stock Prices in Sharia Property and Real Estate Sector Companies Listed on the Indonesian Sharia Stock Index for the Period 2013 - 2022. The research method used is quantitative with a sample of 30 data on 3 companies based on purposive sampling technique. The data analysis used in this research is descriptive statistics, classical assumption test, multiple linear regression, hypothesis testing (t test and f test) and determination coefficient test. The results showed that partially (t) Earning Per Share has a significant effect on stock prices while Sales Growth has no significant effect on stock prices. Simultaneously (f) Earning Per Share and Sales Growth have a significant effect on stock prices. The results of the coefficient of determination test obtained an Adjusted R-squared value of 0.738823, this shows that the ability to explain the independent variables, namely Earning Per Share and Sales Growth on stock prices is 73.88% while the remaining 26.12% is explained by other variables not tested in this study.